2021
DOI: 10.5498/wjp.v11.i11.1075
|View full text |Cite
|
Sign up to set email alerts
|

CPEB1, a novel risk gene in recent-onset schizophrenia, contributes to mitochondrial complex I defect caused by a defective provirus ERVWE1

Abstract: BACKGROUND Schizophrenia afflicts 1% of the world population. Clinical studies suggest that schizophrenia patients may have an imbalance of mitochondrial energy metabolism via inhibition of mitochondrial complex I activity. Moreover, recent studies have shown that ERVWE1 is also a risk factor for schizophrenia. Nevertheless, there is no available literature concerning the relationship between complex I deficits and ERVWE1 in schizophrenia. Identifying risk factors and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 52 publications
(81 reference statements)
2
12
0
Order By: Relevance
“…Consistent with our previous study [ 12 , 13 , 15 , 16 ], we also observed an increased levels of ERVWE1 mRNA and protein in schizophrenia patients ( Figure 1 H–I, Table S9 ). Further analysis revealed that miR-141-3p was positively correlated with ERVWE1 mRNA level ( p < 0.001, Figure 1 J).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with our previous study [ 12 , 13 , 15 , 16 ], we also observed an increased levels of ERVWE1 mRNA and protein in schizophrenia patients ( Figure 1 H–I, Table S9 ). Further analysis revealed that miR-141-3p was positively correlated with ERVWE1 mRNA level ( p < 0.001, Figure 1 J).…”
Section: Resultssupporting
confidence: 93%
“…But in some condition, certain ERVs are activated by external (ultraviolet (UV) [ 57 ], smoking [ 57 ], infections [ 58 ], and chemical drugs [ 59 ]), internal (morphogens, hormones, cytokines, and gene mutation), and epigenetic factors (DNA methylation and histone modification), which will ultimately cause diseases, MS [ 60 ], cancer [ 10 ], and schizophrenia [ 7 , 12 , 13 , 15 , 16 ]. HERVs contribute to development of disorders in various ways, such as assembling viral particles [ 2 ], acting as a promoter to regulate the expression of nearby cellular genes [ 8 ], or expressing viral proteins to regulate host cell signaling networks [ 12 , 13 , 15 , 16 , 61 , 62 , 63 , 64 , 65 ]. Our studies suggest an abnormal expression of ERVWE1 in schizophrenia [ 12 , 13 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations